2013
DOI: 10.1016/j.colsurfb.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure of collagen type I gel cross-linked with gold nanoparticles

Abstract: Scanning electron microscopy, transmission electron micrsocopy, rheomerty, and electrochemistry were used to provide insight into the microstructure of collagen type I gel (1% w/v) modified with the tiopronin-protected (N-(2-mercaptopropionyl)glycine) gold nanoparticles (TPAu), a multivalent crosslinker. The cross-linking reaction, performed via EDC (1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide) coupling, results in compliant, mechanically stable and continuous gels. The gels contain unusual interconnected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…All collagens were like a soft white sponge with a loose and porous structure observed by the naked eye. The SEM results indicated that the surfaces of ASC and PSC were partially wrinkled; it is likely that water was sublimed during lyophilization . However, there were some differences in the structures between ASC and PSC under SEM.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All collagens were like a soft white sponge with a loose and porous structure observed by the naked eye. The SEM results indicated that the surfaces of ASC and PSC were partially wrinkled; it is likely that water was sublimed during lyophilization . However, there were some differences in the structures between ASC and PSC under SEM.…”
Section: Resultsmentioning
confidence: 96%
“…The SEM results indicated that the surfaces of ASC and PSC were partially wrinkled; it is likely that water was sublimed during lyophilization. 36 However, there were some differences in the structures between ASC and PSC under SEM. Figure 4A shows that ASC-s was rugose, similar to an irregular dense sheet-like film.…”
Section: Sem Of Lyophilized Collagenmentioning
confidence: 99%
“…To achieve a homogeneous matrix containing small pores suitable for drug delivery applications and a small size dispersion of the pores, the entire fibrillar component of the collagen has to be removed and only molecular collagen can be used for matrix preparation (9). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the improvement of thermal stability and mechanical strength of the collagen gel is essential. From the previous studies, cross‐linking was a common method to enhance the thermal stability and mechanical strength of collagen during fibril formation (Schuetz et al, ). EDC (1‐ethyl‐3‐(3‐dimethylaminopropyl)‐carbodiimide), one of the zero‐length cross‐linkers which facilitates the direct conjugation of carboxyl to amine and does not become part of the final protein (Velmurugan, Jonnalagadda, & Nair, ), was used as the cross‐linking reagent for this study.…”
Section: Introductionmentioning
confidence: 99%
“…thermal stability and mechanical strength of collagen during fibril formation (Schuetz et al, 2012). EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide), one of the zero-length cross-linkers which facilitates the direct conjugation of carboxyl to amine and does not become part of the final protein (Velmurugan, Jonnalagadda, & Nair, 2013), was used as the cross-linking reagent for this study.…”
mentioning
confidence: 99%